2022
DOI: 10.3390/jcm11226719
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Continuous Renal Replacement Therapy with the oXiris Hemofilter on Critically Ill Patients: A Narrative Review

Abstract: Critically ill patients with sepsis and severe COVID-19 are commonly characterized by a dysregulated immune response and an acute kidney injury. Continuous renal replacement therapy (CRRT) is now proposed as a promising adjuvant therapy to treat these critically ill patients by removing cytokines, pathogen-associated molecular patterns, and damage-associated molecular patterns from the blood. Although multiple hemofilters, including high-cutoff membranes, the oXiris hemofilter, the CytoSorb hemoadsorption devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Indeed, a failure to show a survival effect by a certain therapeutic regimen does not simply mean that the regimen is worthless. Future randomized controlled trials should also assess different primary endpoints, such as the number of ventilation-free days, vasopressor therapy-free days, and ICU-free days and the changes of plasma inflammatory mediators, to shed light on other important effects of EBP on critically ill patients [ 7 , 114 ]. Taken together, the removal of DAMPs during extracorporeal blood purification in critically ill patients with immune dysregulation should be individualized and dynamically changed, and adequate selection of the patient population, treatment dose and type of hemofilters is critically needed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, a failure to show a survival effect by a certain therapeutic regimen does not simply mean that the regimen is worthless. Future randomized controlled trials should also assess different primary endpoints, such as the number of ventilation-free days, vasopressor therapy-free days, and ICU-free days and the changes of plasma inflammatory mediators, to shed light on other important effects of EBP on critically ill patients [ 7 , 114 ]. Taken together, the removal of DAMPs during extracorporeal blood purification in critically ill patients with immune dysregulation should be individualized and dynamically changed, and adequate selection of the patient population, treatment dose and type of hemofilters is critically needed.…”
Section: Discussionmentioning
confidence: 99%
“…Further clinical studies are urgently needed to evaluate the impact of the use of the AN69ST membrane to remove HMGB1 on patient-centered clinical outcomes. As the polyethyleneimine layer of the AN69ST membrane can also adsorb heparin to allow heparin priming before use [ 7 ], it is also of clinical significance to further determine whether the use of the AN69ST hemofilter is able to remove positively charged histones by the primed heparin layer from the blood of critically ill patients receiving continuous renal replacement therapy.…”
Section: Removal Of Hmgb1 and Histones By Hemofiltration Or Hemoperfu...mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the surface is pre-connected with heparin to facilitate anticoagulation in extracorporeal circulation, enhancing the hemocompatibility and biocompatibility of the membrane material. 45 The oXiris membrane material is already available in Europe and China, and several small clinical studies and randomized controlled animal trials have confirmed its good clinical hemodialysis performance. 46 In 2017, Wang et al 47 fabricated a thin film nanofiber composite (TFNC) membrane with a two-layer composite structure for hemodialysis.…”
Section: The Isopropyl Groups In Psf Dialysis Membranes Can Generatementioning
confidence: 99%
“…The AN69 membrane is symmetric and homogeneous with a high density of medium-sized pores, making it highly permeable not only to large solutes but also to the fluid. Uniquely, the AN69 membrane is able to remove low/medium-molecular-weight β 2 -microglobulin and inflammatory cytokines by membrane adsorption through electrostatic binding with negative sulfonic groups as well as by transmembrane transport [ 29 ]. Owing to these unique membrane characteristics, the latest surface-treated AN69 membrane, namely the oXiris membrane, has been widely used for RRT of critically ill patients with sepsis or COVID-19 [ 29 ].…”
Section: Introductionmentioning
confidence: 99%